2022
DOI: 10.5194/hess-26-4323-2022
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking global hydrological and land surface models against GRACE in a medium-sized tropical basin

Abstract: Abstract. The increasing reliance on global models to address climate and human stresses on hydrology and water resources underlines the necessity for assessing the reliability of these models. In river basins where availability of gauging information from terrestrial networks is poor, models are increasingly proving to be a powerful tool to support hydrological studies and water resources assessments (WRA). However, the lack of in situ data hampers rigorous performance assessment, particularly in tropical bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…The larger uncertainty of GRACE data for smaller catchments is often used as an argument for working with large catchments (Bai et al., 2018; Liu et al., 2022), and recent work by Bolaños Chavarría et al. (2022) showed that for many models it becomes challenging to reproduce total water storage if basins are smaller than 60,000 km 2 . Independent of catchment area, work with Australian catchments showed that the AWRA model (Australian Water Resources Assessment system) had most difficulties in reproducing total water storage in western and central Australia (Van Dijk et al., 2011), which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The larger uncertainty of GRACE data for smaller catchments is often used as an argument for working with large catchments (Bai et al., 2018; Liu et al., 2022), and recent work by Bolaños Chavarría et al. (2022) showed that for many models it becomes challenging to reproduce total water storage if basins are smaller than 60,000 km 2 . Independent of catchment area, work with Australian catchments showed that the AWRA model (Australian Water Resources Assessment system) had most difficulties in reproducing total water storage in western and central Australia (Van Dijk et al., 2011), which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the model properly represented ET and TWSA seasonality and long-term variability, while model performances slightly decreased for their deviations from seasonality, coherently with previous literature. Bolaños Chavarría et al (2022) for instance showed that a set of global hydrological and land surface models well represented TWSA seasonality and long-term variability in a tropical river basin in Colombia, but not the TWSA monthly time series that account for the deviations from seasonality. However, model capabilities in simulating TWSA anomalies were comparable during moderate droughts and a severe drought.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…This highlights that evaluating hydrological models against multiple hydrological fluxes and states may represent a way to analyse causes of poor model transferability, verify model internal consistency and so move towards more robust modelling (Guo et al, 2017). Today ET and TWSA remote sensing-based products can be particularly useful for model evaluation, especially for distributed models (Rakovec et al, 2016b;Hulsman et al, 2021;Bolaños Chavarría et al, 2022) as they allow to check also their spatial representativeness. Nonetheless, assessment of model transferability to severe droughts using independent and spatially distributed ET and TWSA remote sensing-based products is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that evaluating hydrological models against multiple hydrological fluxes and states represents a way to analyze causes of poor model performances and hence move towards more robust modelling [31]. ET and TWS remote sensing-based products can be particularly useful for distributed model evaluation [32,33] as they allow to check also the spatial representativeness of models.…”
Section: Introductionmentioning
confidence: 99%